Liquidity Risk and Return to Islamic Interbank Money Market Development - Mochamad Malik Akbar Rohandi (Jurnal Manajemen Bisnis Performa, 2019)
The low interest of Islamic banking in managing its liquidity risk management on Islamic Interbank Money Market (IIMM) has led to sluggish development of IIMM. The purpose of this study is to determine the effect of risk management of Islamic banking liquidity, determine the factors that cause the relationship of influence between the management of liquidity risk and IIMM Return, and knowing the prospects of risk management issues of Islamic bank liquidity concern to the development of IIMM. This research use descriptive and ARCH and GARCH. The results show the variant of EGARCH (1,1) as the best model with R2 1.44%. The Factors affect to IIMM are FDR, STM and Return.Keywords: IIMM Volume, Liquidity Risk, STM and FDR Risk, Return, ARCH and GARCH.